Business Studies in Secondary Schools: Exploring the Teaching and Learning Strategies in Oyo State, Nigeria - Ojelade, Mathew Ojeleke; Ishola, James Aransiola; Ajayi, Johnson Kolawole; Amusat, Rasaq Bamidele; Ahmed, Jeleel Abioye (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The aim of this research was to investigate the teaching methods used by teachers to effectively teach business principles to high school students in the Oke-ogun region of Oyo State, Nigeria. The study includes all the teachers and students in the secondary schools of Oyo State, Nigeria. According to the Post Primary School Management Board (PPSMB), there are 342 secondary schools in Oyo State for the 2023/2024 academic session. The research was conducted in the Oke-ogun region of Oyo State, Nigeria, which comprises 10 local government areas. The researchers purposefully chose 2 pilot schools from each local government, making a total of 20 secondary schools. The JSS 3 students were the target respondents. The study used a well-structured questionnaire and a simple random sampling technique to draw a sample size of 400 (20 students per school). The data collection instrument used was the “Business Studies in Secondary Schools: Exploring the Teaching and Learning Strategies in Oyo State, Nigeria Questionnaire.” The research questions were analyzed using Mean and Standard Deviation. It was found out in the study that the students had not been introduced to the innovative and effective methods mentioned in this research. The teachers were less familiar with strategies like experiential learning, financial literacy, cooperative learning, and integration of soft skills, as indicated in this study, and as a result, these strategies were not in use. Teachers of business studies in Oyo State secondary schools should be provided with more effective contemporary teaching strategies through regular conferences, workshops, seminars, lectures, and symposia, among others to ensure effective service delivery